PENGEMBANGAN MODEL ASESMEN PEKERJAAN SOSIAL UNTUK ANAK YANG BERHADAPAN DENGAN HUKUM MELALUI ASESMEN MODEL KANVAS - Pujileksono Sugeng; Yudi Harianto Cipta Utama; Sari Dewi Poerwanti (Politeknik Kesejahteraan Sosial Bandung, 2022)
This research is motivated by the high number of cases of children in conflict with the law (ABH) and the need to develop an assessment model for ABH. Assessment is the first step for social work professional help, prior to intervention and intervention plans. The ultimate goal of this research is to produce a new model in the implementation of social work assessment for ABH. The model development was carried out by modifying the Biopsychosocial spiritual model assessment (BPSS) with the Business Model Canvas. The model offered is expected to provide benefits and convenience for Pekerja Sosial ABH who handle ABH in conducting assessments of perpetrators, victims, and witnesses who are still children. The aims of this study were: (1) to design the initial assessment model for ABH, (2) to test the ABH Canvas Model Assessment, (3) to make the final model of the Canvas Model Assessment for ABH. This type of research is development research with 10 steps of development research according to Borg and Gall (2007). The model trial was carried out three times, namely trial I (Pekerja Sosial ABH Malang Raya) with an average value of instrument validation of 82.5 (Appropriate). Trial II (Pekerja Sosial ABH East Java) with an average value of instrument validation 84.25 (Appropriate). Trial III (Pekerja Sosial ABH outside East Java Province) with an average validation value of 87.25 (Appropriate). In conclusion, the assessment canvas model for ABH is feasible to be applied as a tool for conducting assessments and preparing social reports for ABH. The advantage of this model is that it adds an educational aspect to the BPSS assessment component and can be used for quick assessments. The weakness of this model is that it is only used for ABH, not for the characteristics of other pediatric clients